2002
DOI: 10.1097/00002030-200208160-00003
|View full text |Cite
|
Sign up to set email alerts
|

Indinavir inhibits sterol-regulatory element-binding protein-1c-dependent lipoprotein lipase and fatty acid synthase gene activations

Abstract: Indinavir inhibits important effector genes of the SREBP-1c pathway, explaining major HAART-related adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 44 publications
3
23
0
1
Order By: Relevance
“…However, studies have reported an alteration in SREBP-1c expression or function in response to other PIs. Dowell et al (31) have shown that nelfinavir inhibits accumulation of mature 68-kDa SREBP-1c protein in 3T3-L1 cells, whereas indinavir induces an abnormal sequestration of SREBP-1c at the nuclear membrane (32,34) and inhibits the expression of SREBP-1c target genes (35). Finally, HIV-infected patients treated with a combination of NRTIs and PIs have a greatly reduced SREBP-1c expression in lipoatrophic superficial fat depots (37).…”
Section: Effects Of Efavirenz On Preadipocytes and Adipocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have reported an alteration in SREBP-1c expression or function in response to other PIs. Dowell et al (31) have shown that nelfinavir inhibits accumulation of mature 68-kDa SREBP-1c protein in 3T3-L1 cells, whereas indinavir induces an abnormal sequestration of SREBP-1c at the nuclear membrane (32,34) and inhibits the expression of SREBP-1c target genes (35). Finally, HIV-infected patients treated with a combination of NRTIs and PIs have a greatly reduced SREBP-1c expression in lipoatrophic superficial fat depots (37).…”
Section: Effects Of Efavirenz On Preadipocytes and Adipocytesmentioning
confidence: 99%
“…In this regard, contradictory results have been published, few studies showing a positive effect (27) and more numerous ones showing a negative effect (28 -33) of PIs on adipocyte differentiation. The inhibitory effects of PIs on adipogenesis have been related to a decreased expression in C/EBP␣ (31) or PPAR␥ (31,32) or to an altered expression or intranuclear localization of SREBP-1c (32,34,35). Interestingly, abnormal changes in SREBP-1c were also found in white adipose tissue of ritonavirtreated mice (36) and in lipoatrophic tissue from HIV-infected patients under HAART (37).…”
mentioning
confidence: 99%
“…27 Studies from cell culture and animal models have shown that PI administration may result in an increased hepatic de novo lipogenesis and cholesterol synthesis through suppression of sterol regulatory element binding protein 1 (SREBP-1). 61 Protease inhibitor treatment may also prevent apolipoprotein B degradation with an ensuring potential for increased secretion of apolipoprotein B-containing lipoproteins.…”
Section: Pathogenesis Of Antiretroviral-induced Metabolic Disordersmentioning
confidence: 99%
“…89 PIs also appear to directly inhibit glucose uptake by insulin-sensitive tissue and cause the accumulation of sterol regulatory element-binding protein-1c (SREBP-1c), which is an important regulator of triglycerides, cholesterol and insulin metabolism in adiopocytes. 90 ApoC-III, an inhibitor of lipoprotein lipase, and apoEcontaining lipoproteins are increased with the use of PIs. 59 Such particles are atherogenic and have been postulated as being implicated in the HIV-associated lipodystrophy and hypertriglyceridaemia.…”
Section: Aetiology Of Human Immunodeficiency Virus-related Lipodystrophymentioning
confidence: 99%